Stable isotopes reveal different dependencies on benthic and pelagic pathways between Munida gregaria ecotypes - Funes, Manuela (2018)
Forage species are key nodes in the energy fluxes between benthic and pelagic zones. The squat lobster, Munida gregaria, is a common forage species of the Southern Hemisphere and its abundance is increasing. This species presents two ecotypes: one (subrugosa) that settles on the sea bottom immediately after the metamorphosis and another (gregaria) that remains in the water column for a variable period of time, before adopting a benthic habit. Hypotheses on its settlement are conflicting; one proposes that it is a density-dependent process of the sea bottom and the other that it is regulated by the availability of pelagic food. To rule out whether feeding factors could be significant in the decision-making process, the first step is to identify whether the ecotypes have different diets or not. This study compared the isotopic niche location, the trophic levels and the reliance on benthic or pelagic resources between ecotypes. Among all sampling events, the isotopic niches of the gregaria and the subrugosa ecotypes were significantly distant from each other. In addition, the difference in δ13C values between ecotypes covered an average of 75% of the total difference between pelagic and benthic pathways. Benthic individuals relied mostly on benthic animals, while pelagic individuals relied on pelagic primary producers. Overall, results show that each ecotype feeds mainly on different energy pathways. Considering its feeding ecology and movements during life history, M. gregaria is a key component of bentho-pelagic coupling.